Zakat Fitrah (Kajian Hadis Tematik) - Syarifuddin Syarifuddin (Universitas Islam Negeri Alauddin, 2013)
Zakat fitrah constitutes the obligatory of every Moslem based on some hadis using the phrase umara or faradha. Hadis about zakat fitrah is shahih, either form. Its sanad or matn. Zakat fitran is very benefial for individuals to enlighten his soul after doing the fast during Ramahan, beside; it is also useful for social necessity.